The Gene Expression of the Main Lipogenic Enzymes is Downregulated in Visceral Adipose Tissue of Obese Subjects - Ortega, Francisco J.; Mayas, Dolores; Moreno‐Navarrete, José M.; Catalán, Victoria; Gómez‐Ambrosi, Javier; Esteve, Eduardo; Rodriguez‐Hermosa, Jose I.; Ruiz, Bartomeu; Ricart, Wifredo; Peral, Belen; Fruhbeck, Gema; Tinahones, Francisco J.; et al. (Obesity (Silver Spring, Md.), 2010)
Contradictory findings regarding the gene expression of the main lipogenic enzymes in human adipose tissue depots have been reported. In this cross‐sectional study, we aimed to evaluate the mRNA expression of fatty acid synthase (FAS) and acetyl‐CoA carboxilase (ACC) in omental and subcutaneous (SC) fat depots from subjects who varied widely in terms of body fat mass. FAS and ACC gene expression were evaluated by real time‐PCR in 188 samples of visceral adipose tissue which were obtained during elective surgical procedures in 119 women and 69 men. Decreased sex‐adjusted FAS (−59%) and ACC (−49%) mRNA were found in visceral adipose tissue from obese subjects, with and without diabetes mellitus type 2 (DM‐2), compared with lean subjects (both P < 0.0001). FAS mRNA was also decreased (−40%) in fat depots from overweight subjects (P < 0.05). Indeed, FAS mRNA was significantly and positively associated with ACC gene expression (r = 0.316, P < 0.0001) and negatively with BMI (r = −0.274), waist circumference (r = −0.437), systolic blood pressure (r = −0.310), serum glucose (r = −0.277), and fasting triglycerides (r = −0.226), among others (all P < 0.0001). Similar associations were observed for ACC gene expression levels. In a representative subgroup of nonobese (n = 4) and obese women (n = 6), relative FAS gene expression levels significantly correlated (r = 0.657, P = 0.034; n = 10) with FAS protein values. FAS protein levels were also inversely correlated with blood glucose (r = −0.640, P = 0.046) and fasting triglycerides (r = −0.832, P = 0.010). In conclusion, the gene expression of the main lipogenic enzymes is downregulated in visceral adipose tissue from obese subjects.